LAYANAN PENGADUAN KERUSAKAN PENERANGAN JALAN UMUM MENGGUNAKAN KODE QR DAN CHAT OTOMATIS DINAS PERHUBUNGAN - Hamzah, Rizki Maulana; Maryana, Sufiatul; Anggraeni, Irma (J-Icon : Jurnal Komputer dan Informatika, 2024)
This research was motivated by observation data which showed results regarding difficulties in receiving complaints from the public, especially regarding damage to Public Street Lighting (PJU). The method used was direct observation at the research site using the SDLC (System Development Life Cycle) model with 6 stages of the SDLC model. that is; Planning, System Analysis, System Design, Implementation, Testing, Validation and Maintenance. In its development, this research used the Google spreadsheet application to create worksheets electronically and Gmail to manage messages electronically. This service has several benefits, including helping in inputting data for reports or public complaints, minimizing the risk of data loss and saving time, as well as making it easier to access information quickly. The results of the research obtained are to create a PJU damage complaint service using QR codes and automatic chatbots to simplify the complaint process and as a medium for complaints as a means of information and cooperation with the public if there is damage to traffic facilities, especially Public Street Lighting (PJU). Trials were carried out at 10 (ten) pole points in different regions, 5 poles in Jasinga and 5 poles in the Jonggol area, their function was to find out whether this complaint service was running well or not. The results of trials carried out in 2 different areas of this complaint service can function well.